TiO2 A semiconductor photocatalyst - Azrina, Abd Aziz; Fatema, Khatun; Minhaj, Uddin Monir; Lan Ching, Sim; Kah Hon, Leong (InTechOpen, 2022)
Titanium dioxide (TiO2) is considered as an inert and safe material and has been used in many applications for decades. TiO2 have been widely studied, due to its interesting general properties in a wide range of fields including catalysis, antibacterial agents, in civil as nano-paint (self-cleaning) and especially photocatalysis, and that affect the quality of life. Thus, the development of nanotechnologies TiO2 nanoparticles, with numerous novel and useful properties, are increasingly manufactured and used. TiO2 doped with noble metal are good candidates in the performance these applications. The fascinating physical and chemical features of TiO2 depend on the crystal phase, size and shape of particles. For example, varying phases of crystalline TiO2 have different band gaps that rutile TiO2 of 3.0 eV and anatase TiO2 of 3.2 eV, determine the photocatalytic performance of TiO2. This chapter explains basic information on TiO2 and theoretical concepts of nanostructure of TiO2 nanoparticles as a semiconductor photocatalyst.